INCREASING STUDENT LEARNING OUTCOMES IN SOCIOLOGY THROUGH MIND MAPPING METHOD - Arini, Yeni (Transpublika Publisher, 2022)
This study aimed to investigate the impact of the Mind Mapping approach on the learning outcomes of seventh-grade students at SMP Negeri 8 SBI Yogyakarta throughout the 2020/2021 academic year. This is a pre-experimental study with a One-Group Pretest-Posttest Design. Using observation, tests, and documentation to collect data. The data analysis process involved descriptive and inferential analysis. The participants in this study were seventh-grade SMP Negeri 8 SBI Yogyakarta students. The results indicated that the learning outcomes of seventh-grade students prior to utilizing the Mind Mapping approach were 66 and after using the Mind Mapping method they were 81,2. This figure demonstrates that the Mind Mapping approach has an effect on the learning outcomes of seventh-grade Sociology students at SMP Negeri 8 SBI Yogyakarta, and the results of the hypothesis test (t-test) indicate a significance level of 0.000; therefore, hypothesis h1 is accepted. On the basis of the foregoing research findings, it can be concluded that the Mind Mapping approach has an effect on the learning outcomes of Sociology students in seventh grade at SMP Negeri 8 SBI Yogyakarta.